Sosialisasi Kesadaran Literasi Menuju Kekuatan Komunitas - Syamsu Hidayat; Filda Angellia; Waskita Cahya; Astried Silvanie; Hafizah Rifiyanti; Yuli Prasetya; Rino Subekti (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
This community service activity aims to enhance the understanding of residents in the Jagakarsa, South Jakarta, regarding the meaning and importance of literacy, particularly in facing the challenges of the digital information era. The underlying problem addressed in this activity is the low level of literacy awareness among the community, as indicated by the tendency to accept and spread information without verification, the lack of a reading culture, and limited understanding of various types of literacy, such as media, digital, and financial literacy. To overcome these issues, the team of lecturers conducted a literacy outreach activity using a casual discussion method, which was chosen for its effectiveness in reaching the community in an informal and communicative setting. The materials presented included the definition of literacy, the importance of filtering information, how to verify the accuracy of news, and the role of families in fostering a culture of literacy. The activity involved residents from diverse backgrounds and was conducted interactively, where participants were not only passive listeners but also engaged in active discussions and shared personal experiences related to literacy challenges. The results showed that the residents responded positively to the outreach, gained new insights, and expressed a commitment to start applying a culture of literacy within their families and communities. This activity demonstrates that a simple yet well-targeted approach can have a tangible impact in raising literacy awareness at the grassroots level.